Analisis Kebutuhan Media dalam Mengatasi Sampah Plastik serta Menumbuhkan Sikap Peduli Lingkungan - Milania, Riandita (Pena Edukasia, 2022)
This study aims to determine the media needed to deal with plastic waste in three elementary schools, including Kalikalong 01 State Elementary School, Sambiroto 01 State Elementary School, and Tayuwetan 02 State Elementary School located in Pati Regency. The background behind this is plastic waste that has not been managed optimally by the school, especially students. This is important because it can reduce plastic waste and care for students in the surrounding environment. This type of research is aqualitative research with data collection in the form of questionnaires and documentation. The subjects of this study were the first to sixth grade teachers who teach in the three elementary schools. From the research results, educators have understood the processing of plastic waste, namely the manufacture of ecobricks. However, the manufacture of ecobricks does not yet have a manufacturing guide that can be implemented for students.